A Review of Children First and Keeping Safe Training in Ireland: Implications for the Future. Issue 2 (2nd April 2016) - Devaney, Carmel; McGregor, Caroline
ABSTRACT: The aim of this paper is to report on the evaluation of two standardised training programmes provided by the statutory children and family service in the Republic of Ireland in 2012. This involved an evaluation of Children First Basic Level Training, which was delivered to all staff employed in the statutory services, and Keeping Safe, Basic Level Training, which was delivered externally to those working with children and families in voluntary and community services. The objectives of this review were: to determine the perceived need of all participants on both training programmes; to establish the relevance of the training programmes vis-à-vis the participants work practice; to evaluate whether both training programmes have met their stated aims; and to establish the necessary components of a training programme to inform future development. This retrospective review was conducted using mixed methods. The findings show that, in the main, the needs of the respondents were met by the training. Most respondents agreed that the training met its aims and was relevant. Valuable suggestions were made regarding development for the future. However, due to an unexpectedly low response rate to the research, the low sample size has meant that we cannot deduce that the mostly positive results are representative of participants in the training programmes as a whole. However, while not a reliable representation of the whole trainee population, the findings are nonetheless illustrative and instructive as a guide within this complex and important field for the development of future training. It is concluded that given the ongoing challenge of protecting children from abuse and neglect, the findings will inform a renewed commitment to ongoing development of generic training as well as the development of more advanced methods of evaluation, and increased engagement of training participants in the research process.